Encyclopaedia of religion and ethics; v. 11 - Hastings, James; Selbie, John A.; Gray, Louis H. (Edinburgh, Scotland T and T Clark, 1926)
Contents : v. 11 : Sacrifice - Sudra
Keywords: Religion; Ethics